2020
DOI: 10.1002/jbmr.4272
|View full text |Cite
|
Sign up to set email alerts
|

The HIF-PHI BAY 85-3934 (Molidustat) Improves Anemia and Is Associated With Reduced Levels of Circulating FGF23 in a CKD Mouse Model

Abstract: Fibroblast growth factor‐23 (FGF23) is a critical factor in chronic kidney disease (CKD), with elevated levels causing alterations in mineral metabolism and increased odds for mortality. Patients with CKD develop anemia as the kidneys progressively lose the ability to produce erythropoietin (EPO). Anemia is a potent driver of FGF23 secretion; therefore, a hypoxia‐inducible factor prolyl hydroxylase inhibitor (HIF‐PHI) currently in clinical trials to elevate endogenous EPO to resolve anemia was tested for effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Importantly, serum phosphate was increased in the Cre + mice, therefore, the level of Fgf23 reductions in bone in these groups of mice had a significant effect on systemic mineral metabolism. Further, as described above, anemia has been recognized as a very strong stimulator of Fgf23 mRNA levels in bone in vivo (Farrow et al, 2011) and in cells (Noonan et al, 2021), and serum phosphate also drives Fgf23 production (Saito et al, 2005). Considering the marked hypoferremia and hyperphosphatemia observed in the conditional‐null mice, although the Dmp1‐Cre is known to efficiently recombine the flox‐Fgf23 allele (Clinkenbeard et al, 2016), the sum of both of these systemic Fgf23 drivers may override the suppressive abilities of the targeted deletion.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Importantly, serum phosphate was increased in the Cre + mice, therefore, the level of Fgf23 reductions in bone in these groups of mice had a significant effect on systemic mineral metabolism. Further, as described above, anemia has been recognized as a very strong stimulator of Fgf23 mRNA levels in bone in vivo (Farrow et al, 2011) and in cells (Noonan et al, 2021), and serum phosphate also drives Fgf23 production (Saito et al, 2005). Considering the marked hypoferremia and hyperphosphatemia observed in the conditional‐null mice, although the Dmp1‐Cre is known to efficiently recombine the flox‐Fgf23 allele (Clinkenbeard et al, 2016), the sum of both of these systemic Fgf23 drivers may override the suppressive abilities of the targeted deletion.…”
Section: Discussionmentioning
confidence: 96%
“…In this regard, we and others previously demonstrated that this model has hypoferremia, as well as reduced hematocrit and hemoglobin, tissue fibrosis, and increased markers of inflammation (Clinkenbeard et al, 2019; Noonan et al, 2020). Previous clinical studies in humans (Wolf et al, 2013) and translational experiments in mice (Farrow et al, 2011), as well as isolated osteoblast/osteocyte cells (Noonan et al, 2021), have also shown that FGF23 is driven by anemia/hypoxia (Clinkenbeard et al, 2019). Studying mice with CKD under dual conditions of treatment with exogenous iron on a genetic background of conditional Fgf23 deletion was another strength of this work, providing a unique opportunity to dissect phenotypes downstream of anemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relevant genes include hepcidin ( HAMP ), heme oxygenase-1 ( HMOX1 ), aconitase ( IRP1 ) and erythropoietin ( EPO ). Importantly, HIF1α activation modulates both extra- and intracellular iron levels by regulating the expression of the transport protein transferrin (TF, encoded by TF gene), and cell surface transferrin receptor 1 protein (TFR1, encoded by the TFRC gene) ( Cheng et al, 2015 ; Muckenthaler et al, 2017 ; Chen et al, 2020 ; Noonan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%